2020
DOI: 10.1111/acel.13213
|View full text |Cite
|
Sign up to set email alerts
|

SS‐31 and NMN: Two paths to improve metabolism and function in aged hearts

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 45 publications
4
43
0
Order By: Relevance
“…The National Institutes of Health and other organizations have made it a priority to fund research into microvascular contributions to the pathogenesis of VCI and AD, including the role of hypertension-induced microvascular damage. New therapeutic strategies aimed at reversing ageing-induced and hypertension-induced cardiovascular and cerebromicrovascular impairment include use of mitochondrial antioxidants 153 , 179 , polyphenols and other activators of NRF2 and sirtuin 1 (refs 150 , 180 ), senolytics 181 184 , anti-inflammatory interventions 185 , agents that rescue cellular energetics 128 , 186 and/or prevent cellular NAD + depletion 135 , 152 , AMPK activators 187 and mTOR inhibitors 188 .…”
Section: Future Perspectivesmentioning
confidence: 99%
“…The National Institutes of Health and other organizations have made it a priority to fund research into microvascular contributions to the pathogenesis of VCI and AD, including the role of hypertension-induced microvascular damage. New therapeutic strategies aimed at reversing ageing-induced and hypertension-induced cardiovascular and cerebromicrovascular impairment include use of mitochondrial antioxidants 153 , 179 , polyphenols and other activators of NRF2 and sirtuin 1 (refs 150 , 180 ), senolytics 181 184 , anti-inflammatory interventions 185 , agents that rescue cellular energetics 128 , 186 and/or prevent cellular NAD + depletion 135 , 152 , AMPK activators 187 and mTOR inhibitors 188 .…”
Section: Future Perspectivesmentioning
confidence: 99%
“…NMN likely has a different mechanism of action than SS-31, as it works on NAD + biosynthesis to enhance mitochondrial function. 117 Because NMN and SS-31 work via distinct mechanisms, Whitson et al combined SS-31 and NMN treatments and reported that the two drugs in combination were more effective in treating heart dysfunction than either alone. 117 This provides new insight into treatment of tendinopathy by protecting mitochondria via NAPDH synthesis.…”
Section: Mitochondrial Protectants As Therapeutic Agentsmentioning
confidence: 99%
“…NMN appeared to have a greater acute effect on the heart than SS‐31 in this study. NMN likely has a different mechanism of action than SS‐31, as it works on NAD + biosynthesis to enhance mitochondrial function 117 . Because NMN and SS‐31 work via distinct mechanisms, Whitson et al .…”
Section: Mitochondrial Protectants As Therapeutic Agentsmentioning
confidence: 99%
“…Nutritional stress, in the form of high sugar and fat diets, synergizes with aging to drive tissue dysfunction. Old mice on a short-term high sugar diet show cardiac hypertrophy which is attenuated by elamipretide (otherwise known as SS-31, a small peptide that modifies mitochondrial function) treatment [ 4 , 32 ]. Surprisingly, a high fat diet is protective against age-associated skeletal muscle sarcopenia and promotes fatigue resistance.…”
Section: Session One: Organ Aging and Growth Signalingmentioning
confidence: 99%